A cooperação no estado federal e seus aportes para a política de saúde pública brasileira - Romariz, Erika Doria Romariz (2023)
This dissertation aims to verify if cooperation among members of the Brazilian Federation can impact the conduction of a specific public policy – the one related to the public health system. In order to do so, the first step will be to analyze the distinctive characteristics of the cooperative federation according to an evolutionary and interdisciplinary perspective. This analysis will be based on the assumption that the federative structure allows the territorial distribution of political and legal power by constitutionally guaranteeing self-government, self-management, and self-regulation to its members. If, on the one hand, the members have their own interests, on the other hand they are also committed to the common objectives of the sovereign State. That commitment demands cooperation to promote mutual development, especially in a Welfare State. Once the main attributes of the cooperative archetype are understood, the research will focus on the historical development of federal cooperation in Brazil and its constitutional treatment. The next step will be the study of constitutional standards of public healthcare policy, organized in Brazil as a unified system. In that regard, the examination will show that the operating guidelines of the unified healthcare system (SUS) presuppose a coordinated and cooperative relationship between central and local government. The analysis will emphasize not only the cooperative mechanisms related to the healthcare policy, but also how cooperation can help to promote the right to health. The conclusion will argue the importance of a coordinated action by the different autonomous members of the federation, while recognizing the prevalence of the central government in the conduction of the public policy as a necessary consequence of the unified system